Anaerobic power, muscle strength and physiological changes in physically active men following yogic practice - Pal Rameswar; Saha Mantu; Chatterjee Abhirup; Halder Kaushik; Tomer Omveer Singh; Pathak Anjana; Basavaraddi Ishwar V. (Sciendo, 2014)
Study aim: The present study was aimed to evaluate the effect of three months (90 min daily for five days in a week) yogic practice on physiological and physical parameters of physically active service personnel.